A semiose da linguagem traumática em Rita no pomar - Oliveira, Bruna Belmont de (2015)
The present paper aims at carrying out a reading of the novel Rita no Pomar by Rinaldo Fernandes in the attempt of realizing how the subjectivity of the traumatizing condition is outlined by the protagonist-narrator‘s language. The narrative‘s fragmentation goes along with the reframing of the lived past in São Paulo and at the Pomar beach, places whose involvement with characters and facts are always present in Rita‘s report. Through Charles Sanders Peirce‘s semiotics, we shall analyse how it is organized in the narrative‘s structure the arrangements of the symbolic, indexical and iconic signs in order to produce the effect of discontinuity and anticipation in the plot. With the support of Sigmund Freud‘s psychoanalitic theory, we shall discuss about the trauma and its representation in the novel. We still seek to investigate the presence of the movement attraction-rejection, a recurrent image in the structural and fictional levels, as well as in the macrostructre of the work, as an icon for Trauma.